Karya Tari Dewaruci Sebagai Tari Sesaji Dalam Rangka Dies Natalis Isi Surakarta - Nuryanto, Nuryanto (Acintya, 2023)
The dance work Dewaruci is a new work inspired by Bima's attitude and character in wayang so that it is danced in the dashing male dance of the Surakarta style. The make-up and fashion design refer to the wayang orang characters in the Surakarta style. The purpose of the research entitled Dewaruci Dance Work is to describe the dashing Surakarta style dance used as offering dance at the Surakarta Indonesian Institute of the Arts (ISI) Anniversary ceremony in 2015. The research method of the Surakarta Style Dewaruci Dance Work is a type of qualitative research. Narrative data sources. Data analysis techniques use form and content. Data obtained from observation studies, interviews and documentation. The results of the research, the Dewaruci Dance Work is a themed group dance danced by seven dashing male dancers, as a symbol of the attitude and behavior of the academic community who have reached the age of 51. The gallant movements reflect valor, perseverance, honesty, firmness in studying and practice knowledge so that it is beneficial to society. The movement begins with offerings accompanied by Yogyan Pelog Nem Sieve.Keywords: dashing, dance, offerings, anniversary